A new species of genus Thoradonta Hancock, 1908 (Orthoptera: Tetrigoidea: Tetrigidae) from India - Gupta, Sunil Kumar; Shi, Jian-Ping; Chandra, Kailash (Zootaxa, 2018)
A new species of genus Thoradonta subtruncata sp. nov. is described from Korba, Chhattisgarh, India. A brief comparison with the reference collection Thoradonta spiculoba Hancock, 1912 present in National Zoological Collection identified by Prof. K. K. Günther. The new species Thoradonta subtruncata sp. nov. is similar to Thoradonta spiculoba Hancock, 1912, but differs from latter by median carina of vertex distinct and elevated, facial carinae slightly sinuated between antennae, scutellum moderate near median ocellus, tegmen elongate, more punctuate, narrow in middle, apex subtruncate and pulvilli III distinctly longer than length of I and II pulvilli.